2007
DOI: 10.1016/j.jpsychores.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and markers of inflammation and coagulation in depressed patients with coronary heart disease

Abstract: The finding that fibrinogen and IL-6 are moderately related to HRV suggests a link between these factors in depressed CHD patients. The relationship between ANS function and inflammatory and coagulant processes should be investigated in larger mechanistic studies of depression and cardiac morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 27 publications
(26 reference statements)
3
63
1
1
Order By: Relevance
“…Dysregulation of the hypothalmic-pituitary-adrenal axis in depressed states may also play a role, particularly with regard to effect on stress responses, either biochemically with inflammatory cytokine imbalances or clinically through abnormalities of BP and heart rate (28)(29)(30). Furthermore, autonomic nervous system dysfunction may accompany depression, further exacerbating BP and heart rate dysregulation and potentially manifesting with reduced heart rate variability and cardiac baroreflexes that may further aggravate cardiovascular morbidity (31)(32)(33). While inflammation and autonomic dysfunction are not uncommon in patients undergoing HD (34,35), depression may represent an aggravating factor toward greater morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the hypothalmic-pituitary-adrenal axis in depressed states may also play a role, particularly with regard to effect on stress responses, either biochemically with inflammatory cytokine imbalances or clinically through abnormalities of BP and heart rate (28)(29)(30). Furthermore, autonomic nervous system dysfunction may accompany depression, further exacerbating BP and heart rate dysregulation and potentially manifesting with reduced heart rate variability and cardiac baroreflexes that may further aggravate cardiovascular morbidity (31)(32)(33). While inflammation and autonomic dysfunction are not uncommon in patients undergoing HD (34,35), depression may represent an aggravating factor toward greater morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the HRV indexes have been used to understand various conditions, such as coronary artery disease [54][55][56][57], cardiomyopathy [26.58], arterial hypertension [29,[59][60][61], myocardial infarction [62][63][64], sudden death [65], chronic obstructive pulmonary disease [2,66,67], renal failure [68], heart failure [69], diabetes [70], stroke [71], Alzheimer's disease [72] leukemia [73], obstructive sleep apnea [74], epilepsy [75], headache [76], among others.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Table 2 shows studies using HRV in various physiological and pathological conditions. Carnethon et al [56] Novais et al [29] Menezes et al [60] Terathongkum et al [61] Takahashi et al [55] Bittencourt et al [26] Pecyna [63] Carney et al [54] Limongelli et al [58] Karas et al [59] Larosa et al [62] Javorka et al [38] Catai et al [7] Weerapong et al [41] Mello et al [37] Paschoal et al [72] Sin DD et al [66] Kudaiberdieva et al [65] Lopes et al [71] Neves et al [73] Furuland et al [68] Lopes et al [79] and Paschoal et al [80] observed that the aging process causes a depletion of vagal tone and consequent increase in sympathetic activity, therefore older individuals have a lower HRV. In 2006, Rajendra Acharya et al [4] observed that HRV is lower with age and the variation is greater in women.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…2 Depression has been linked to having a higher number of Framingham risk factors (i.e., smoking, obesity, sedentary lifestyle) for cardiac disease in patients with diabetes. 3 Depression is also associated with physiologic dysregulation of the hypothalamic-pituitary axis (HPA) 4 and sympathetic nervous system 5,6 as well as an increase in inflammatory markers, 7,8 which may also adversely affect the course of diabetes. Given the adverse effect on self-care and physiologic dysregulation, it is not surprising that longitudinal studies have also shown that depression is linked with an increased risk of microvascular and macrovascular complications.…”
Section: Introductionmentioning
confidence: 99%